Retroperitoneal Fat Necrosis in Response to an Episode of Acute Pancreatitis. (24th September 2021) - Gilani, M. B.; Akcan, T.; Peterson, M.; Zahid, A.
Abstract : Acute pancreatitis can result in fat necrosis, typically occurring in the peripancreatic region within weeks to months, and it generally appears as a low attenuation collection, with minimal heterogeneity. There are no specific imaging features that can diagnose retroperitoneal fat necrosis which may imitate other entities including certain malignancies, which may lead to invasive studies for diagnosis. Herein, we present a case of extensive retroperitoneal fat necrosis beyond the peripancreatic region that developed 10 days after an episode of acute pancreatitis.